The origins of ISIS: the collapse of nations and revolution in the Middle East - Mabon, Simon (I.B. Tauris, 2017)
The rapid expansion of ISIS and its swathe of territorial gains across the Middle East have been headline news since 2013. Yet much media attention and analysis has been focussed upon the military exploits, brutal tactics and radicalisation methods employed by the group. While ISIS remains a relatively new phenomenon, it is important to consider the historical and local dynamics that have shaped the emergence of the group in the past decade. In this book Simon Mabon and Stephen Royle provide the reader with a comprehensive overview of the roots, tactics and ideology of the group, exploring the interactions of the various participants involved in the formative stages of ISIS. Based on original scholarly sources and first-hand research in the region, this book provides an authoritative and closely-analysed look at the emergence of one of the defining forces of the early twenty-first century